ENhAncing Lifestyle Behaviors in EndometriaL CancEr (ENABLE): A Pilot Randomized Controlled Trial. (January 2022) - Edbrooke, Lara; Khaw, Pearly; Freimund, Alison; Carpenter, Danielle; McNally, Orla; Joubert, Lynette; Loeliger, Jenelle; Traill, Anya; Gough, Karla; Mileshkin, Linda; Denehy, Linda
Purpose: Endometrial cancer is associated with the highest comorbid disease burden of any cancer. The aim of this trial was to assess the feasibility and safety of an allied health intervention during adjuvant treatment. Methods: A mixed-methods pilot randomized (2:1) controlled trial with concealed allocation and assessor-blinding. Eligibility criteria: adjuvant endometrial cancer treatment scheduled, disease stage I-IIIC1, ECOG 0-2 and able to perform unsupervised physical activity (PA). Participants received usual care and 8 sessions of weekly, individualized, lifestyle education (diet and PA) with behavior change and social support (intervention group), delivered predominantly by telehealth, or usual care alone. Feasibility outcomes: recruitment and consent rates, decline reasons, program acceptability, intervention adherence and retention. Results: 22/44 eligible patients (50%, 95%CI: 36%, 64%) were recruited over 10 months (14 intervention, 8 usual care). The recruitment rate was 2.2 patients/month (95%CI: 1.4, 3.3). Patients who declined had too much going on (7/22, 32%) or were not interested (6/22, 27%). Mean (SD) age and BMI were 63.2 years (6.8) and 31.9 kg/m 2 (6.7). A majority were FIGO stage I (15/22, 68%) and received vaginal brachytherapy (14/22, 64%). Adherence was high, 11/14 (79%, 95%CI: 52%, 92%) participants attended >70% of scheduled sessions. Retention was 100% (95%CI: 85%, 100%) at 9 weeks, however completion of objective measures was impacted by COVID-19 restrictions. Telehealth and online questionnaires enabled participation. No serious adverse events occurred. Conclusion: The intervention was acceptable to participants with high levels of adherence and retention. Trial findings will be used to design a future RCT. Trial registration: The trial was registered onwww.anzctr.org.au (ACTRN12619000631101) 29/04/2019.